Education on the “Sifat Dua Puluh of Allah” in the Book Fawakih al-Janani by Al-Haj Abdul Rashid - Sri Hartati Adiningsih; Qanithah Fairus Azzahrah (Jurnal Impresi Indonesia, 2026)
This study analyzes Aqidah education on the "sifat dua puluh of Allah" in the book Fawakih al-Janani by Al-Haj Abdul Rashid, focusing on its pedagogical content and teaching methods. The research is motivated by the lack of academic studies examining Aqidah teaching methods in Nusantara scholarly literature, and by the tendency to regard the "sifat dua puluh of Allah" as less relevant to contemporary Islamic education. As a work that played a significant role in transmitting Ash'ariyyah theology among the Malay community—particularly in traditional Islamic boarding schools and madrasas—this book warrants closer scholarly attention. Using a library research method with a content analysis approach, the study finds that Aqidah education in Fawakih al-Janani is presented through a systematic and contextual pedagogical framework, comprising: (1) the use of simple and communicative Malay-Jawi as a medium for teaching Aqidah; (2) a hierarchical arrangement of material progressing from Sifat Nafsiyah, Sifat Salbiyah, and Sifat Ma'ani to Sifat Ma'nawiyah; and (3) the integration of naqli (textual) and 'aqli (rational) proofs to strengthen students' understanding of creed. The teaching further emphasizes the principle of tanzih (the glorification of Allah) and the rejection of tashbih (likening Allah to His creation). This study concludes that Fawakih al-Janani not only functions as a creed instruction text but also represents an effective and relevant model of traditional Islamic creed education applicable to contemporary contexts.